2013
DOI: 10.1523/jneurosci.0528-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α3 Is Required for Late Postnatal Stability of Dendrite Arbors, Dendritic Spines and Synapses, and Mouse Behavior

Abstract: Most dendrite branches and a large fraction of dendritic spines in the adult rodent forebrain are stable for extended periods of time. Destabilization of these structures compromises brain function and is a major contributing factor to psychiatric and neurodegenerative diseases. Integrins are a class of transmembrane extracellular matrix receptors that function as αβ heterodimersand activate signaling cascades regulating the actin cytoskeleton. Here we identify integrin α3 as a key mediator of neuronal stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 103 publications
(186 reference statements)
3
66
0
Order By: Relevance
“…The result is RhoC-ROCK-mediated LIMK activation and cofilin phosphorylation (inactivation) outside of invadopodia and active cofilin concentrated at the invadopodium core, where RhoC is inactive (Bravo-Cordero et al, 2011). Interestingly, β1 integrin induces Arg-dependent p190RhoGAP phosphorylation and activation in fibroblasts and neurons (Bradley et al, 2006; Kerrisk et al, 2013; Warren et al, 2012). Thus, it will be interesting to explore the possibility that β1 integrin-Arg signaling may act as a master upstream regulator of invadopodial cofilin activity through Arg-mediated phosphorylation of both cortactin on Y421 and p190RhoGAP at the invadopodia core to relieve cortactin- and RhoC-dependent suppression of cofilin activity, respectively.…”
Section: Invadopodium Maturationmentioning
confidence: 99%
“…The result is RhoC-ROCK-mediated LIMK activation and cofilin phosphorylation (inactivation) outside of invadopodia and active cofilin concentrated at the invadopodium core, where RhoC is inactive (Bravo-Cordero et al, 2011). Interestingly, β1 integrin induces Arg-dependent p190RhoGAP phosphorylation and activation in fibroblasts and neurons (Bradley et al, 2006; Kerrisk et al, 2013; Warren et al, 2012). Thus, it will be interesting to explore the possibility that β1 integrin-Arg signaling may act as a master upstream regulator of invadopodial cofilin activity through Arg-mediated phosphorylation of both cortactin on Y421 and p190RhoGAP at the invadopodia core to relieve cortactin- and RhoC-dependent suppression of cofilin activity, respectively.…”
Section: Invadopodium Maturationmentioning
confidence: 99%
“…Reductions in phospho-p190RhoGAP, as following CORT exposure, are associated with increased RhoA activity (Hernandez et al, 2004; Sfakianos et al, 2007; Warren et al, 2012; Kerrisk et al, 2013). Accordingly, we found that phosphorylation of cofilin, a major down-stream target of RhoA-ROCK signaling, is also increased following CORT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our group has identified an integrin-Abl2/Arg kinase-p190RhoGAP cascade that attenuates RhoA-ROCK signaling to stabilize hippocampal CA1 dendrite arbors (Moresco et al, 2005; Sfakianos et al, 2007; Warren et al, 2012; Kerrisk et al, 2013; Lin et al, 2013; Koleske, 2013). The current study provides evidence that CORT exposure disrupts this dendrite stabilization pathway.…”
Section: Introductionmentioning
confidence: 99%
“…There are 24 known integrin heterodimers of αβ subunits, and a subset of these are expressed in the brain, including in the hippocampus, cortex, thalamus, and cerebellum (Chan et al, 2003; Dansie and Ethell, 2011; McGeachie et al, 2011). In neurons, some integrins are enriched at synaptic membranes and localized to the postsynaptic density of dendritic spines (Bernard-Trifilo et al, 2005; Bourgin et al, 2007; Chavis and Westbrook, 2001; Kerrisk et al, 2013; Mortillo et al, 2012; Pinkstaff et al, 1999; Warren et al, 2012). In particular, integrin subunits α3, α5, α8, α(V), β1, and β3 function in a variety of roles in the brain, including neuronal migration, synapse and dendrite development, morphogenesis and stability, and synaptic plasticity (Gupton and Gertler, 2010; McCarty et al, 2005; Rehberg et al, 2014; Wu and Reddy, 2012).…”
Section: Integrinsmentioning
confidence: 99%
“…Genetic disruption of integrin α3 from mice compromises hippocampal LTP, synapse and dendrite stability, and animal behavior (Chan et al, 2003, 2007; Kerrisk et al, 2013), but does not impact paired-pulse facilitation (PPF), a parameter sensitive to changes in presynaptic neurotransmitter release probability (Chan et al, 2003). Reducing the gene dosage of integrins α3 and α5 together is sufficient to cause defects in PPF, while simultaneous reduction of integrin α3, α5, and α8 gene dosage in a triple heterozygous animal yields defects in spatial memory and hippocampal LTP (Chan et al, 2003).…”
Section: Integrinsmentioning
confidence: 99%